THE EFFECT OF BRAND AWARENESS AND ELECTRONIC SERVICE QUALITY ON LOYALTY OF E-COMMERCE CUSTOMERS - Frans Sudirjo; Arief Yanto Rukmana; Syarifuddin Syarifuddin; Sudadi Pranata; Munir Tubagus (Jurnal Scientia, 2023)
The purpose of this study is to ascertain how client loyalty in the marketplace is impacted by brand awareness and the caliber of electronic services. Research of this kind is referred to as quantitative research. The sample for this study included up to 100 respondents who were students who had utilized e-commerce at least twice. Both incidental sampling and nonprobability sampling were used in the sampling strategy. Results of questionnaires that were delivered to respondents online through Google Form were used as the major source of data for this study. While this is happening, secondary data takes the shape of linked documentation. Then, multiple linear regression analysis, the classical assumption test, and instrument test analysis were used to analyze the data that had been obtained. The findings of this study suggest that customer loyalty is positively and significantly influenced by brand awareness and the quality of electronic services. This is demonstrated by the t test results, which have significance levels of 0.000 0.05 for the brand awareness variable and less than 0.05 for the electronic service quality variable